Pengaruh net profit margin, return on asset, current ratio dan earning per share terhadap harga saham pada perusahaan makanan dan minuman yang terdaftar di Bursa Efek Indonesia (BEI) Periode 2016-2020 - Suryawuni, Suryawuni; Lilia, Wirda; Stevia Lase, Mutiara; Purnama Sari Br Bangun, Nisa; Cella Elena, Gres (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2022)
This research aims to know about the influence of net profit margin, return on assets, and current ratio. Earnings per share on the stock price of food and beverage sub-sector company on the Indonesia Stock Exchange in 2016-2020. The data used is sourced from financial data on the Indonesia Stock Exchange through the websiteÂ www.IDX.co.idÂ and has been selected based on predetermined criteria. The population used in this study were food and beverage companies, totaling 28 companies, using a purposive sample. The samples obtained were 14 companies. With this research, it can become a science to help further researchers and students or the general public who need a source of information. The study shows that net profit margin, return on assets, current ratio, and earnings per share have a positive and significant effect simultaneously on the stock price. Net profit margin, return on assets, and earnings per share partially positively and significantly affect the stock price. At the same time, the current ratio variable has no significant effect on stock price in food and beverage companies listed on the Indonesia Stock Exchange from the 2016 to 2020 period.Â